Pediatric Sickle Cell Disease in Sudan: Complications and Management - Meysaa Talha; Bashier Osman; Safa Abdalla; Hind Mirghani; Iman Abdoon (Anemia)
Background. Sickle cell disease (SCD) is a life-threatening genetic disorder due to the formation of sickle hemoglobin molecule (HbS) that polymerizes in hypoxic conditions leading to SCD-related complications. Different approaches have been used in the management of SCD including symptomatic management, supportive management, and preventive management. Objectives. To assess the management of SCD in pediatric patients in Gaafar Ibnauf Referral Hospital in Khartoum locality, Sudan. Method. A descriptive, retrospective, hospital-based study was conducted in Gaafar Ibnauf Hospital using a data collection sheet. The study included all medical files of pediatric patients with SCD attending the hospital during the period from the first of April 2018 to the first of July 2018. The data were analyzed using descriptive statistics and the chi-square test. P<0.05 was considered statistically significant. Results. Out of 207 pediatric patients, 53.1% were females (mean age of 7.5 ± 3.1 years), with a 1.1 : 1 female:male ratio and low socioeconomic status. Only 4.3% of participants had health insurance. The Messeryia tribe in western Sudan had the highest prevalence of the disease among the Sudanese tribes (11.1%). Vaso-occlusive crisis (33.3%), infections (13.5%), and neurological complications (10.6%) were the most frequent complications reported during routine visits. After initiation of management, only 3.4% of pediatric patients had hemolytic crises, and 1.4% of the anemic patients had splenomegaly. 100% of patients received folic acid, 73.9% used hydroxyurea, and 69.6% underwent blood transfusion for the management of SCD. Prophylactic penicillin was prescribed for 15% of patients, and 41.1% were immunized with pneumococcal vaccine (PPSV23). Most patients had been scheduled for planned follow-up visits every 3–6 months (93.2%). Hydroxyurea and blood transfusion significantly reduced fever and vaso-occlusive crisis. Conclusion. The SCD treatment protocol in Gaafar Ibnauf Children’s Hospital, involving preventive and symptomatic therapy, is consistent with the internationally implemented protocols for SCD management. However, immunization and prophylactic penicillin approaches are deficient.